Platelet-Rich Plasma for Sport-Active Patients with Knee Osteoarthritis: Limited Return to Sport. (31st January 2020) - Altamura, Sante Alessandro; Di Martino, Alessandro; Andriolo, Luca; Boffa, Angelo; Zaffagnini, Stefano; Cenacchi, Annarita; Zagarella, Maria Stella; Filardo, Giuseppe
Abstract : Objective . To evaluate a cohort of sport-active patients suffering from cartilage degeneration and OA, in terms of clinical outcome and return to sport (RTS) after platelet-rich plasma (PRP) injective treatment. Design . This study included forty-seven sport-active patients ≤50 years old with unilateral symptomatic knee cartilage degeneration or OA. Patients received 3 PRP injections and were prospectively evaluated at baseline and then at 2, 6, 12, and 24 months follow-up by IKDC subjective EQ-VAS, and Tegner scores. Furthermore, patients were asked about their RTS, in terms of return to any sport level or to their activity level before symptoms onset. Results . IKDC subjective score improved significantly at all follow-ups, changing from 59.2 ± 13.6 to 70.6 ± 13 at 12 months and to 76.7 ± 12.5 at 24 months (p < 0.0005 ). A similar outcome was observed with the EQ-VAS score. Tegner score improved from 3.6 ± 1.4 to 4.8 ± 0.9 at 24 months (p < 0.0005 ), but only 76.6% of patients returned to some sport activity and 48.9% to the same activity level. A lower presymptoms Tegner score was associated with a higher RTS rate, both at any level (p = 0.024 ) and at the same presymptoms level (p < 0.0005 ). Conclusions . Sport-active patients affected by knee OA can benefit from PRP injections, with pain and function improvement over time. However, results are less satisfactory in terms of RTS since only half can achieve the same sport level as before the onset of symptoms. Patients undergoing PRP treatment should be made aware of their low chances to go back to high-impact sport activities.